Performance Evaluation and Optimization of Binder-Toner and Mixing Efficiency Ratios in an E-Waste Toner-Modified Composite Mixture Using Response Surface Methodology - Syyed Adnan Raheel Shah; Sabahat Hussan; Nabil Ben Kahla; Muhammad Kashif Anwar; Mansoor Ahmad Baluch; Ahsan Nawaz (Infrastructures)
E-waste toner (EWT), which is produced in large quantities by modern industries, has the potential to be utilized as a bitumen modifier to improve engineering properties and save costs. The current study focuses on exploring the optimization of EWT content to identify the most optimal proportions for achieving desirable levels of mechanical properties. This study also examined the effects of E-waste toner contents ranging from 0% to 30% on the fresh consistency of toner-modified and unmodified binder. The study utilized a central composite design (CCD) together with the response surface methodology (RSM) to optimize the mix design variables, specifically the binder-toner ratio (BT) and mixing efficiency ratio (MER). The objective of this study was to examine the combined effects of these variables on the mechanical characteristics of EWT-modified asphalt mixtures. The mechanical responses were obtained through the performance of four responses such as Marshall stability (MS), Marshall flow (MF), indirect tensile strength (ITS), and stiffness tests. The findings suggest that the combined interaction of BT and MER ratios has an impact on their mechanical characteristics. However, the BT ratios had a significant impact on the volumetric attributes compared to MER. The RSM-based prediction models had an R-square over 0.86 across each response. This demonstrates that the inclusion of BT and MER ratios were accountable for a minimum of 86% of the alterations in the mechanical characteristics of EWT-modified asphalt. The multi-objective optimization analysis determined that the optimal proportions for the EWT-modified asphalt, in order to obtain the ideal consistency, were 0.249 ratio of BT and 1.63 ratio of MER with a desirability value of 0.97. Overall, it was found that RSM is a reliable technique for precisely forecasting the mechanical properties of EWT-modified asphalt, including BT and MER ratios.